2007
DOI: 10.1093/jjco/hym132
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of O6-Methylguanine-DNA Methyltransferase Protein Expression in Patients with Recurrent Glioblastoma Treated with Temozolomide

Abstract: Background: Temozolomide (TMZ) is active against newly diagnosed glioblastoma (GBM), and O 6 -methylguanine-DNA methyltransferase (MGMT) is implicated in resistance to TMZ and nitrosoureas. We evaluated the efficacy and safety of the standard 5-day TMZ regimen in patients with recurrent GBM after initial therapy including nitrosourea-based chemotherapy, in conjunction with an analysis of the prognostic value of MGMT protein expression regarding response to TMZ and survival. 2 /day of TMZ for five consecutive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 41 publications
(47 reference statements)
2
28
0
5
Order By: Relevance
“…Both trials used a schedule of TMZ 150-200 mg/m 2 for 5 out of 28 days. Other prospective studies mainly without previous TMZ treatment using this schedule showed similar PFS-6 rates ranging from 21 to 24% [64][65][66][67].…”
Section: Temozolomide Monotherapy and Combination Regimensmentioning
confidence: 52%
“…Both trials used a schedule of TMZ 150-200 mg/m 2 for 5 out of 28 days. Other prospective studies mainly without previous TMZ treatment using this schedule showed similar PFS-6 rates ranging from 21 to 24% [64][65][66][67].…”
Section: Temozolomide Monotherapy and Combination Regimensmentioning
confidence: 52%
“…Wiewrodt et al (Wiewrodt et al, 2008) showed that patients expressing p30 fmol mg À1 MGMT protein in the pre-treatment tumour volume had a significantly better response to alkylating therapy than those with MGMT protein above this level. Others have shown that patients with low MGMT protein expression had significantly improved survival compared with those with high expression (Brell et al, 2005;Chinot et al, 2007;Nagane et al, 2007). Vlassenbroeck et al (Vlassenbroeck et al, 2008) used a real-time MSP assay to determine a clinically relevant cut-off for stratification of glioblastomas into two distinct populations, with prognostic significance in recurrent anaplastic astrocytoma but not glioblastomas treated with temozolomide (Sadones et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The absolute value of MGMT mRNA seems to coincide more with enzyme activity than with DNA methylation status. In contrast, an analysis at the protein level of MGMT 20 determined that immunohistochemistry shows low specificity and is also not quantitative. Although mRNA levels measured by RT-PCR may not always correlate with enzyme activity, MGMT activity itself seems to be more strongly correlated with clinical resistance to nitrosoureas than to mRNA expression.…”
Section: Discussionmentioning
confidence: 97%